Crenças de alunos brasileiros que vivem na fronteira Brasil/ Venezuela a respeito do processo de ensino/ aprendizagem de espanhol como língua estrangeira - Lima, Mara Gardeane Abreu (2015)
This ethnographic qualitative research aims to identify and understand the beliefs of Brazilian students who live in Brazil/Venezuela border regarding the teaching/learning process of Spanish as a foreign language. The research was conducted in a public school located in Pacaraima city - Brazil. To achieve the main goal, observations were made in and out of the classroom during the months from March to October of 2014 and interviews with nine high school students. The theoretical basis of this research is based on studies in Applied Linguistics regarding beliefs (Almeida Filho, 2003; Barcelos, 1995, 2004, 2007.2011; Silva, 2005, 2008). The questions that guided this study were: 1. What are the beliefs of Brazilian students of a public school in Brazil /Venezuela border context about the process of teaching and learning Spanish as a foreign language? 2. What are the beliefs of Brazilian students about the Spanish spoken in the Venezuelan border? 3. How do the students beliefs, mentioned above, influence the Spanish learning process as a foreign language? The results suggest that pointing the grammar as a pillar of language learning has contributed to construct beliefs that seem to influence negatively not only on the process of learning the Spanish language in school, but also in relation to Venezuelan variant spoken in Brazil / Venezuela border, focus of this research.